The Effect of Sustainability on Market/BV: A Study on Public Companies in Indonesia in 2013-2019 - Gracia Shinta S. Ugut; Zabrina Raissa (Budapest International Research and Critics University, 2021)
The objective of this study is to know is ESG score has an influence towards Market/BV. The dependent variable in this study is market/bv. The control variables in this study are: (1) return on equity (ROE), (2) debt to asset ratio (D/A), (3) earnings per share growth (EPS growth). This study used 55 populations of publicly listed companies in Indonesia that were listed on the Indonesia Stock Exchange from 2013 to 2019 with a purposive sampling method. The total sample in this study was 385 data which were processed using the multiple linear regression analysis methods with a fixed-effect model, which had been tested both the Chow test and the Hausman test. The results of this study indicate that the ESG score disclosure has a negative and significant effect on Market/BV.